PARAMETRIC REPRESENTATION AND BIFURCATION ANALYSIS OF THE CUBIC EQUATION SOLUTIONS WITH APPLICATION TO THE PHASE TRANSITIONS - Alexandr A. BARSUK (Studia Universitatis Moldaviae: Stiinte Exacte si Economice, 2019)
Real solutions representation for the cubic equation with real coefficients in a parametric form is given. The dependence of the solutions on the equation coefficients and the bifurcation conditions for these solutions are studied. In the parametric space regions with one and three real solutions are considered. Using parametric representations of the cubic equation solutions, the stability and bifurcation conditions of the equilibrium states for the thermodynamic systems described by the Landau-type kinetic potential are analyzed.   REPREZENTAREA PARAMETRICĂ ȘI ANALIZA BIFURCAȚIONALĂ A SOLUȚIILOR ECUAȚIEI CUBICE CU APLICARE LA TRANZIȚIILE DE FAZĂ Este expusă reprezentarea soluțiilor reale pentru ecuația cubică cu coeficienți reali într-o formă parametrică. Sunt studiate dependența soluțiilor de coeficienții ecuației și condițiile de bifurcație pentru aceste soluții. În spațiul parametric sunt considerate regiuni cu una și trei soluții reale. Folosind reprezentările parametrice ale soluțiilor ecuației cubice, sunt analizate condițiile de stabilitate și de bifurcație ale stărilor de echilibru pentru sistemele termodinamice descrise de potențialul cinetic de tip Landau.